2016
DOI: 10.1016/j.scitotenv.2016.05.099
|View full text |Cite
|
Sign up to set email alerts
|

Predicting environmental mitigation requirements for hydropower projects through the integration of biophysical and socio-political geographies

Abstract: Uncertainty about environmental mitigation needs at existing and proposed hydropower projects makes it difficult for stakeholders to minimize environmental impacts. Hydropower developers and operators desire tools to better anticipate mitigation requirements, while natural resource managers and regulators need tools to evaluate different mitigation scenarios and order effective mitigation. Here we sought to examine the feasibility of using a suite of multi-faceted explanatory variables within a spatially expli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
(65 reference statements)
0
7
0
Order By: Relevance
“…We found that hydropower operations can have various and somewhat unexpected impacts on reservoir fish populations, as illustrated by the positive and interacting effects of WLR magnitude on brown trout biomass and density. Therefore, when designing management policies to meet the future demands for renewable energy, biogeographic, climatic, socio-political and other relevant gradients should be considered to appropriately balance energy generation needs and goals for minimizing environmental impacts and social conflicts (DeRolph et al, 2016). As noted here, one of the complicating factors for hydropower management and policymaking is the dynamic nature of the causal interactions between drivers of hydropower operations and ecosystem impacts.…”
Section: Study Limitations and Applicationsmentioning
confidence: 99%
“…We found that hydropower operations can have various and somewhat unexpected impacts on reservoir fish populations, as illustrated by the positive and interacting effects of WLR magnitude on brown trout biomass and density. Therefore, when designing management policies to meet the future demands for renewable energy, biogeographic, climatic, socio-political and other relevant gradients should be considered to appropriately balance energy generation needs and goals for minimizing environmental impacts and social conflicts (DeRolph et al, 2016). As noted here, one of the complicating factors for hydropower management and policymaking is the dynamic nature of the causal interactions between drivers of hydropower operations and ecosystem impacts.…”
Section: Study Limitations and Applicationsmentioning
confidence: 99%
“…<1 MW and >1300 MW, relicenses, and PSH), and utilizing more extensive environmental mitigation categories. Additionally, our study complements the Schramm et al (2016) and Derolph et al (2016) studies by evaluating the economics of environmental mitigation.…”
Section: Existing Studies Of Hydropower Environmental Mitigation Measuresmentioning
confidence: 96%
“…Their findings suggest that the majority of FERC mitigation requirements are related to either hydrologic flows or recreation, and that hydropower plants with the highest number of mitigation measures are found in the Pacific Northwest. These authors then conducted a complementary study (Derolph et al, 2016) and developed predictive models for identifying potential environmental mitigation requirements at proposed hydropower sites using this previously collected data. The models utilize a wide variety of site-specific input variables, from biological and hydrologic conditions to recreational uses, to predict potential mitigation requirements for a potential hydropower site.…”
Section: Existing Studies Of Hydropower Environmental Mitigation Measuresmentioning
confidence: 99%
See 2 more Smart Citations